An Experiment on Gender Representation in Majoritarian Bargaining - Andrzej Baranski; Diogo Geraldes; Ada Kovaliukaite; James Tremewan (Utrecht University, Utrecht University School of Economics (U.S.E.), 2021)
Does the gender composition of committees affect negotiations in majoritarian bargaining? We report the results of an experiment in which subjects are placed in triads to negotiate the division of a sum of money under majority rule and the gender composition of the group is manipulated, ranging from all female (FFF), female majority (FFM), male majority (MMF), to all male (MMM). Results show that men are more likely to make the opening offer, and contrary to our hypothesis, agreements are reached fastest in MMM and slowest in FFF. The proportion of grand coalitions is increasing in the number of females while minimal winning coalitions (MWCs) increase monotonically in the number of males. MWCs are disproportionately more likely to be same-gender in MMF, which leads to a gender gap in earnings compared to FFM. When provisional MWCs form prior to a final agreement, excluded men are more proactive than excluded women in attempting to break the coalition by making alluring offers, which partially explains why mixed gender MWCs are less frequent in MMF compared to FFM. Notably, some females adopt male-type behavior in MMF regarding their initial proposals and aggressiveness when left out from a MWC.
Keywords: 330; Unstructured bargaining; gender differences; experiment